Pragmatikus cselekvéselmélet - a kollektív cselekvés mint egyéni káros szenvedély eredményének elmélete - Kreutz, Henrik; Földvári, Mónika (Szociológiai Szemle, 2024)
Starting with the typology of action as conceived by Max Weber the explication of the terms introduced by him shows that these concepts are by far too crude and that he omitted several important types of action. On the one side affective behaviour and emotional action have to be differentiated since the latter is by no means irrational. Fritz Heider for example spoke of a "logic of emotions" decades ago. On the other side rationality in the sense of "Zweckrationalität" has to be conceived as a form of addictive behaviour. It is true, as Gary S. Becker has shown, that we can speak of "rational addiction", but it is clear that if a person becomes totally dependent on a drug or an ideological goal, his behaviour becomes self-destruvtive and this can hardly be named "rational". A third serious problem of Weber’s typology of action is, that he never made quite clear what a "value rational" (wertrational) action means. On the basis of the so called "pattern variables", defined by Talcott Parsons, and his theory of socialization an attempt is made in this article to deliver an explication of the term of "Wertrationalität" (value-rationality). On the basis of the 5 pattern variables, each being conceived as consisting of five dichotomies, 32 possible action orientations are derived and some of these can be identified as different types of rationality. If we conceive "Wertrationalität" and "Zweckrationalität" on this basis we find, that "value rationality" always implies a more complicated calculation than "Zweckrationalität". Furthermore, it implies often enough, that not all the means should be used, even if a person could dispose of them. Seen on the short run, "value-rational" orientation therefore implies a handicap if a person has to compete with a "zweckrational" actor. Therefore one should expect an evolutionary process by which "value-rational" actors are omitted from the social system as "loosers". A detailed analysis shows, however, that persons with a universalistic value orientation have a superior chance to form common value systems with those, who are also universalistically oriented, if they act in a value-rational way and that they therefore have superior chances in the competition with "zweckrational" actors on the long run. A second very serious disadvantage of "zweckrational" actors was detected already by Max Weber himself: "Zweckrationalität" itself becomes in its purest form an addiction. Success is sought in this case only because it is successful. If success is the ultimate goal of "zweckrational" orientation for its own sake (as a thrill), action becomes totally irrational. This will be the consequence, because no material goals exist anymore and the ultimate goal of action gets a formal character. Therefore the final result of "zweckrational" action is a basically nihilistic orientation.